Comparative evaluation of the carcinogenic effect of second and third generation combined oral contraceptives in Drosophila melanogaster (Research, Society and Development, 2024)
Objectives: The objective of this work is to comparatively evaluate the carcinogenic effect of contraceptives combined with the progestins levonorgestrel (second generation) and desogestrel (third generation), through the test for detection of epithelial tumors in Drosophila melanogaster. Methods: To this end, three concentrations of the contraceptive combined with ethinylestradiol and levonorgestrel were prepared (C1-0.78/ 3.9 mcg/mL; C2-1.56/ 7.8 mcg/mL and C3-3.12/15.6 mcg/mL) and three concentrations of contraceptive combined with ethinylestradiol and desogestrel (C1-0.78/ 3.9mcg/mL; C2-1.56/ 7.8 mcg/mL and C3-3.12/15.6 mcg/mL), all of which tested isolated from each other. For negative control, Tween 80 (1%) was used, and for positive control, doxorubicin (0.4 mM). Results: The carcinogenic effect was observed only at the highest concentration of the combined contraceptive of ethylniestradiol with desogestrel (C3). All combined contraceptive concentrations of ethinylestradiol and levonorgestrel (C1, C2 and C3) and the lowest concentrations of ethinylestradiol and desogestrel (C1 and C2) had tumor frequencies that did not differ significantly from the negative control. Conclusion: It was concluded that third-generation oral contraceptives showed carcinogenic potential in D. melanogaster, but only at higher concentrations.